Systematic review and meta-analysis of risk factors for postoperative delirium among older patients undergoing gastrointestinal surgery. Issue 2 (16th December 2015) - Scholz, A F M; Oldroyd, C; McCarthy, K; Quinn, T J; Hewitt, J
Abstract: Background: Postoperative delirium (POD) is common after surgery. As age is a known risk factor, the increased ageing of the population undergoing surgery emphasizes the importance of the subject. Knowledge of other potential risk factors in older patients with surgical gastrointestinal diseases is lacking. The aim here was to collate and synthesize the published literature on risk factors for delirium in this group. Methods: Five databases were searched (MEDLINE, Web of Science, Embase, CINAHL® and PSYCinfo®) between January 1987 and November 2014. The Newcastle–Ottawa Scale was used to rate study quality. Pooled odds ratios or mean differences for individual risk factors were estimated using the Mantel–Haenszel and inverse-variance methods. Results: Eleven studies met the inclusion criteria; they provided a total of 1427 patients (318 with delirium and 1109 without), and predominantly included patients undergoing elective colorectal surgery. The incidence of POD ranged from 8·2 to 54·4 per cent. A total of 95 risk factors were investigated, illustrating wide heterogeneity in study design. Seven statistically significant risk factors were identified in pooled analysis: old age, American Society of Anesthesiologists (ASA) physical status grade at least III, body mass index, lower serum level of albumin, intraoperative hypotension, perioperative blood transfusion and history of alcohol excess. Patients with POD had a significantly increased duration of hospital stay and a higher mortality rate compared with those without delirium. Conclusion: Delirium is common in older patients undergoing gastrointestinal surgery. Several risk factors were consistently associated with POD. Abstract : Several significant risk factors